A practical guide to using qualitative research with randomized controlled trials - O'Cathain, Alicia ([Oxford] : Oxford University Press, 2018)
'A Practical Guide to Using Qualitative Research with Randomized Controlled Trials' focuses on qualitative research, emphasizing subjectivity, flexibility, open data collection, depth, and context, and randomized controlled trials (RCTs), emphasizing objectivity, standardization, measurement, and a key goal of bias reduction. The differences between the two methodologies make their combination an interesting `extreme case' of mixed methods research.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 6, 2018).
Keywords: Qualitative research -- Methodology; Clinical trials -- Methodology